Novel Bi2O4/BiOBr heterojunction photocatalysts: In-situ preparation, photocatalytic activity and mechanism. (April 2018) - Wang, Hai Yang; Liu, Zhang Sheng; Guo, Li Tong; Fan, He Liang; Tao, Xue Yu
Abstract: Novel Bi2 O4 /BiOBr heterojunctions were fabricated via a chemical etching process. BiOBr nanosheets could be in-situ generated in Bi2 O4 micro-rods, which greatly improved the interface quality. The photocatalytic performance of samples was evaluated by the degradation of rhodamine B(RhB) and methyl orange (MO) under visible light irradiation. The results showed that Bi2 O4 /BiOBr heterojunctions displayed higher photocatalytic activity than pure Bi2 O4 and BiOBr, and 99.3% MO could be degraded in 60 min over 0.4BB (~ 33.3 mol% BiOBr) sample. The effective separation and transfer of the photogenerated electrons and holes were believed to be the main factor for the enhanced activity, and the holes (h + ) and ·O2 − radicals were confirmed to be the main active species. This work offers an effective route to the fabrication of Bi2 O4 /BiOBr heterojunctions with high interface quality for photocatalytic applications.